THE IMPORTANCE OF LEARNING FOREIGN LANGUAGES - Boltayeva Mexrangiz Xaydarovna (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Learning foreign languages has become an important skill in the modern world, bringing a wide range of personal, professional, and cognitive benefits. As globalization continues to shape society and the economy, the ability to communicate in multiple languages is becoming increasingly valuable. This article discusses the importance of learning foreign languages, its impact on communication, cultural exchange, career opportunities, and cognitive development. With the rise of technology and interdependence in the digital age, learning foreign languages has become not just a luxury, but a necessity. The article also examines current data and trends in language learning, including the influence of social networks, language applications, and the role of foreign language teaching in the academic environment.